Quantitative assessment of ethnomedicinal plants utilized by the Eastern Himalayan tea garden workers, India - Chettri, Deepika; Chowdhury, Monoranjan (Ethnobotany Research and Applications, 2026)
Background: The Eastern Himalaya is rich in diverse flora and is home to indigenous communities. The present study was undertaken to document the understudied traditional medicinal wisdom of tea garden workers in the Eastern Himalayas, India. Methods: Ethnomedicinal surveys and interviews were conducted between 2019 and 2024, involving 127 informants (92 male and 35 female) aged 20–90 years. Data analysis utilised quantitative indices, statistical tools, and the Jaccard index (JI) and Rehman’s Similarity Index (RSI). Results: Informants reported 193 ethnomedicinal plants used to treat 15 disease categories. Leaves represented the most commonly utilised plant part and were generally prepared as decoctions. The highest Informant Consensus Factor (ICF) was associated with bone-related disorders (0.65). Ocimum tenuiflorum demonstrated the highest Use Value (UV) at 0.078. Among the documented plants, 84 showed 100% Fidelity Level (FL), indicating exclusive use; Ocimum tenuiflorum had the lowest FL (7.14%), indicating versatile use. Conclusions: The plants with high Use Value and Fidelity Level can be subjected to further pharmacological studies to validate ethnomedicinal knowledge of the tea garden workers of the Eastern Himalaya. Keywords: Quantitative study, ethnomedicines, tea garden workers, indigenous community, Eastern Himalaya